A Decade of Data from an IVF Center: Factors Contributing to Infertility, Their Prevalence, and Impact on Live Birth Rates - Hale Bayram; Yaprak Dönmez Çakıl; Belgin Selam; Mehmet Cıncık (Journal of Clinical Medicine, 2026)
Background: Infertility is increasingly recognized as a significant global public health concern. A thorough understanding of the diverse causes of infertility and their influence on treatment outcomes is essential for optimizing therapeutic strategies and improving success rates. Methods: In this study, we analyzed data from 9132 couples who underwent IVF treatment at a fertility center in Istanbul, Turkey, between 2010 and 2020. Results: Female factor infertility was the most prevalent among all participants (35.4%), followed by male infertility (26.4%), combined infertility (22.3%), and unexplained infertility (15.8%). Diminished ovarian reserve was found to be the most common indication in the female and combined infertility groups. Embryo transfer (ET) was performed in 7485 cases. Within this cohort, the antral follicle count was higher in the combined and unexplained infertility groups compared with the female and male infertility groups. The highest number of MII oocytes was found in the unexplained infertility group. Pregnancy rates varied significantly across groups, being higher in the male infertility and unexplained infertility groups than in the female infertility and combined infertility groups. Live birth rates also varied significantly across groups. The highest rate was observed in the unexplained infertility group. Conclusions: The distribution of infertility etiologies and their association with ICSI outcomes underscore the necessity to enhance the efficacy of ART protocols and to adopt evidence-based approaches to treatment strategies. Female factor infertility remains a significant clinical challenge, whereas unexplained infertility presents relatively favorable outcomes.